FACTOR X DEFICIENCY IN NORTH PAKISTAN - Anwar, Masood; Hamdani, Syed Naeem Raza; Ayyub, Muhammad; Ali, Waqar (Journal of Ayub Medical College Abbottabad, 2004)
Background: Factor X deficiency is one of the most rare hereditary coagulation disorders. In populations where rate of consanguineous marriages is high, rare hereditary disorders also flourish. Pakistan is one of those countries. The study was conducted to estimate the incidence of factor X deficiency in patients with bleeding disorders in North Pakistan. Methods: The records of the patients referred to Armed Forces Institute of Pathology for investigations of a suspected bleeding disorder were reviewed from 1st January 1997 to 30th June 2002. All patients referred for the investigations of a suspected bleeding disorder were included in the study. All patients underwent clinical interview and examination at the department. Factor X deficiency was diagnosed on the basis of prolonged prothrombin time and prolonged partial thromboplastin time with kaolin, which were corrected by addition of aged serum but not with adsorbed plasma. Factor X assays were carried out where possible. Results: Only 24 patients of factor X deficiency were detected in 571 patients presenting with coagulation disorder. In 4 cases deficiency was thought to be secondary history, clinical findings and lab results. Inherited deficiency of factor X was thus detected in only 20/571 (3.5%) of the patients. Family history was positive in 8/20 (40%) patients. Consanguinity was noted in 12/20 (60%) patients. Median age of patients was 3 years. Male and females were in equal numbers. Most common clinical presentations were prolonged bleeding after trauma and mucosal bleeding seen in 80% and 70% of patients respectively. In patients in whom factor X assay was performed only one had <1% levels. Conclusion: Factor X deficiency although rare in American and European populations is not that rare in this part of the world. Its existence should be kept in mind in patients presenting with mucosal bleeding and prolonged PT and PTTK but normal platelet count and TT. The mutations in factor X, in this part of the world are most probably not the one, which would cause a severe bleeding diathesis. Keywords: Haemophilia, Factor X deficiency, Consanguinity, Inherited coagulopathy